An analytical method for precise determination of the cadmium isotopic composition in plant samples using multiple collector inductively coupled plasma mass spectrometry. Issue 6 (21st March 2015) - Wei, Rongfei; Guo, Qingjun; Wen, Hanjie; Yang, Junxing; Peters, Marc; Zhu, Chuanwei; Ma, Jie; Zhu, Guangxu; Zhang, Hanzhi; Tian, Liyan; Wang, Chunyu; Wan, Yingxin
<x xml:space="preserve">Abstract</x> Three-isotope plots of Cd isotope ratios in plant samples and Cd standard materials are presented in this study.